2014
DOI: 10.1177/0884533614565251
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorus and Calcium

Abstract: Phosphorus (P) and calcium (Ca) serve vital roles in the human body and are essential components of nutrition support therapy. Regulation of P and regulation of Ca in the body are closely interrelated, and P and Ca homeostasis can be affected by several factors, including disease states, clinical condition, severity of illness, and medications. Nutrition support clinicians must understand these factors to prevent and treat P and Ca disorders in patients receiving nutrition support therapy. This review provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…In addition, it was shown that serum calcium concentration and urinary calcium excretion were increased by 3% ferric citrate treatment, being similar with non-clinical study results about ferric citrate hydrate [8]. Phosphorus and calcium homeostasis is strictly regulated mainly by kidney, bone, intestine and parathyroid glands [9]. Increases in serum phosphorus can lead to a decrease in serum ionized calcium.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, it was shown that serum calcium concentration and urinary calcium excretion were increased by 3% ferric citrate treatment, being similar with non-clinical study results about ferric citrate hydrate [8]. Phosphorus and calcium homeostasis is strictly regulated mainly by kidney, bone, intestine and parathyroid glands [9]. Increases in serum phosphorus can lead to a decrease in serum ionized calcium.…”
Section: Discussionsupporting
confidence: 75%
“…The obvious advantages of using serum markers are that they are relatively cheap, easy to obtain, and have a low patient burden. However, serum potassium and phosphate are strongly influenced by non-dietary factors such as residual renal function [ 112 , 113 ], constipation [ 114 ]; adherence to prescribed medications [ 115 , 116 ], acid base balance [ 117 ] and time between treatments [ 118 ], making them unreliable and inaccurate markers of dietary adherence [ 119 121 ]. Future studies of dietary adherence in ESKD should ideally attempt to use direct observation and immediate quantification of dietary intake to provide the most accurate data on dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of phosphorus, especially the role that it plays in the formation of adenosine triphosphate and 3-2 diphosphoglycerate, is related to the point that phosphorus is a very important component of supportive nutrition for patients [ 29 ]. Refeeding syndrome is one of the important issues in the feeding of malnourished patients.…”
Section: Discussionmentioning
confidence: 99%